“Stay committed on the frontlines”: sustainability of the activism of social workers in Guiyang, China - Junling Jin; Sai Tang; Yifu Liu; Xiaoyu Luo (PLoS ONE, 2025)
Social work has played an increasingly important role in social governance, service provision and driving for social change in China. Despite of the advancement of social work at the macro level in the country, substantial challenges remain to the sustainability of activism of social workers under the current social and economic context in China. Yet the fundamental reasons that underpin social workers’ persistence in activism haven’t been well investigated. By following the sustained commitment theory, the researchers investigated how and why frontline social workers sustain their activism over time. Qualitative research was conducted with 15 frontline social workers from local organizations in Guiyang, Guizhou Province, China. The findings highlight the role of “creativity” in maintaining activism of social workers in a way that both challenge and advance the sustained commitment theory. Instead of being confined to a fixed set of creative actions described by the theory, this study stresses the creativity of social workers in addressing challenges and generating feasible strategies in specific contexts. An essential prerequisite “confidence” for creativity in sustaining activism in social work was introduced. This study contributes to a deeper understanding of sustained activism in social work through the lens of social workers and the enhancement of the professional support for social workers in China.